2016
DOI: 10.4049/jimmunol.1502614
|View full text |Cite|
|
Sign up to set email alerts
|

Cutting Edge: Integrin α4 Is Required for Regulatory B Cell Control of Experimental Autoimmune Encephalomyelitis

Abstract: The neutralization of alpha-4 integrin (Itga4) is currently used as treatment in multiple sclerosis. While most studies focused on its function on lymphocyte migration to the central nervous system, we have uncovered the importance of Itga4 expression on B cells for the generation of regulatory B cells in peripheral immune organs and their control of pathogenic T cell response and CNS pathology. Our study underscores the importance of looking at the dual role of B cells in CNS autoimmunity and provides importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
1
18
1
Order By: Relevance
“…Agree with this observation in human patients, mice harbouring a4-integrindeficient B-cells display a significant reduction in disease manifestation upon huMOGinduced EAE model 66 . In contrast to the results observed in MS patients, the genetic deficiency of a4-integrin in B-cells resulted in exacerbated disease manifestation in a pMOG-induced EAE model 67 . Another aspect supporting the idea that huMOG-induced EAE is a proper experimental system to study B-cell participation in MS is based on CXCR3.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Agree with this observation in human patients, mice harbouring a4-integrindeficient B-cells display a significant reduction in disease manifestation upon huMOGinduced EAE model 66 . In contrast to the results observed in MS patients, the genetic deficiency of a4-integrin in B-cells resulted in exacerbated disease manifestation in a pMOG-induced EAE model 67 . Another aspect supporting the idea that huMOG-induced EAE is a proper experimental system to study B-cell participation in MS is based on CXCR3.…”
Section: Discussioncontrasting
confidence: 94%
“…(VCAM-1) expressed in the blood-brain barrier, allowing the lymphocyte infiltration into the CNS 65,66 . It is noteworthy that the genetic deficiency of a4-integrin restricted to the CD19 + B-cells, resulted in exacerbated CNS autoimmunity in a model of pMOG-induced EAE 67 , indicating the high relevance of a4-integrin in the infiltration of regulatory B-cells into the CNS in this EAE model. Accordingly, our results showed that Drd3-deficiency in B-cells not only resulted in impaired a4-integrin expression and reduced B-cell infiltration into the CNS, but also in the accumulation of B-cells with higher immunosuppressive potential (higher il10…”
Section: Discussionmentioning
confidence: 88%
“…(VCAM-1) expressed in the blood-brain barrier, allowing the lymphocyte infiltration into the CNS [65,66]. It is noteworthy that the genetic deficiency of a4-integrin restricted to the CD19 + B-cells, resulted in exacerbated CNS autoimmunity in a model of pMOG-induced EAE [67], indicating the high relevance of a4-integrin in the infiltration of regulatory B-cells into the CNS in this EAE model. Accordingly, our results showed that Drd3-deficiency in Bcells not only resulted in impaired a4-integrin expression and reduced B-cell infiltration into the CNS, but also in the accumulation of B-cells with higher immunosuppressive potential (higher il10 and lower cfs2 transcription) in the periphery.…”
Section: Discussionmentioning
confidence: 89%
“…While germinal center reactions mainly occur in the spleen and lymph nodes, various reports describe formation of functional ectopic lymphoid follicles in the CNS of MS patients and in mice with EAE [ 46 48 ]. Exclusion of B cells from the CNS results in reduced severity of EAE induced by rhMOG yet exacerbates EAE induced by MOG 35-55 peptide, indicating that access to the CNS is required for EAE mediated by B cell antigen presentation yet can also be important for regulatory B cells to ameliorate disease [ 49 51 ]. In contrast, Tesfagiorgis et al found that antigen-nonspecific B cells are recruited to the CNS compartment while myelin-specific B cells remain in the peripheral draining lymph nodes in a model of active EAE that requires B cells [ 52 ].…”
Section: Discussionmentioning
confidence: 99%